Estimation of antioxidative potential of thyme (Thymus alpestris L.) - Vasiljević, Ljubica; Beribaka, Mirjana; Vulinović, Jelena; Petronić, Slađana (Journal of Engineering & Processing Management, 2017)
Family Lamiaceae (labia) includes a large number of cosmopolitan species including Thymus alpestris (Thyme) characterized by the presence of essential oils and phenolic compounds. It represents a perennial semi-shrubby plant. The antioxidant potential of thyme is due to the presence of polyphenolic acids and flavonoids. The topic of this paper is the extraction of thyme (Thymus alpestris) with 40% ethanol and 50% ethanol, using Soxhlet method (circulatory extraction), after which, the content of phenolics and flavonoids was determined in order to confirm the antioxidant potential of this plant species. The results show that 40% ethanol extract has the highest content of phenolics and flavonoids and the highest antioxidant potential, resultingly.